Evidence-based practice in exercise science. The six-step approach - Amonette, W. E.; English, K. L.; Kraemer, W. J. (Human Kinetics, 2016)
Part I: Overview and Historical Background of Evidence-Based Practice Chapter 1. The Need for Evidence-Based Practice in Exercise Science Evidence-Based Practice in Action Defining Evidence-Based Practice Applying Evidence-Based Practice in Exercise Science Team Approach to Evidence-Based Practice Becoming an Evidence-Based Practitioner Chapter 2. The Process of Evidence-Based Practice The Importance of Evidence in Exercise Science Applying the Five Steps of Evidence-Based Practice The Case for Evidence-Based Practice Criticisms of Evidence-Based Practice Chapter 3. Philosophy, Science, and Evidence-Based Practice Epistemology Epistemology of Modern Science The Paradigm of Evidence-Based Practice Chapter 4. Sources of Evidence Sources of Knowledge Types of Evidence Chapter 5. Reading and Interpreting Research Evidence Consumers of Research What is Research? Components of a Research Paper Steps to Critically Reading Research